The Use of Edmodo Media on Digital Literacy in Elementary Schools of 3T Area during The Covid-19 Pandemic - Dian Permatasari Kusuma Dayu; Niken Dwi Setyaningsih (Jurnal Basicedu, 2022)
Coronavirus Disease is an infectious disease that first appeared in Wuhan, China in 2019. The widespread spread of the Covid-19 virus in Indonesia has prompted the government to issue a new policy to break the chain of transmission of the Covid-19 virus, namely by calling for online learning to be carried out at home using internet facilities. However, not all schools in the 3T areas in Indonesia carry out online learning well, many obstacles are encountered, in terms of facilities, teachers and students. There are still many teachers who only often use the online learning media Whatsapp group and many assignments from students are sent through the application. Apart from that, in terms of students, students feel bored with using the media, because they only do discussions and download material without carrying out discussion activities with friends or teachers in online learning. Edmodo is an internet-based platform that provides services to help facilitate teachers delivering material and assignments to students. Research Objectives to determine the effectiveness of Edmodo learning media on digital literacy in 3T regional schools. This type of research uses quantitative research. The results of the study show that the use of Edmodo as an effective learning medium for digital literacy in schools. Edmodo as an E-Learning learning medium has advantages and increases interest in learning and makes the learning atmosphere more enjoyable.